EXPERIMENTAL RESEARCH ON THE INFLUENCE OF 3D PRINTING PROCESS PARAMETERS ON MECHANICAL PROPERTIES OF PRODUCTS - WEI Bin; DING YiHao; LIU XiaoPeng; LI JinHe; YU HongJie (Jixie qiangdu)
In order to explore the effects of material properties, filling density, support structure and other parameters on mechanical properties and strength characteristics of 3 D printed products, an optimization design method of 3 D printed configuration based on strength requirements was proposed. The mechanical properties of the products were obtained through the simulation calculation of the finite element structure strength and the comparative analysis of the tensile test of the characteristic samples. The tensile strength of 3 D printed products with different internal structures has great differences when the packing density is the same. In theoretical analysis and experimental test, the tensile strength of concentric structures is higher, while that of folded lines and spirals is lower. The results have guiding significance for in-depth analysis of the relationship between the strength of 3 D printing parts and the filling structure, and provide research data support for the optimization design of 3 D printing parameters based on strength demand.